2013
DOI: 10.1177/1934578x1300800819
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Contents of Neochlorogenic Acid, Chlorogenic Acid and Three Quercetin Glycosides in Leaves and Fruits of Rowan (Sorbus) Species and Varieties from Collections in Lithuania

Abstract: Our research aim was to investigate the quantitative composition of neochlorogenic acid, chlorogenic acid, rutin, hyperoside and isoquercitrin in leaves and fruit of introduced rowan plants to Lithuania using a HPLC method. In leaf and fruit samples, quantitative estimation of neochlorogenic acid (in leaf samples 1.11-11.49 mg/g, in fruit samples 0.93-5.43 mg/g), chlorogenic acid (in leaf samples 2.74-21.91 mg/g, in fruit samples 0.55-7.50 mg/g), rutin (in leaf samples 0.03-4.88 mg/g, in fruit samples 0.02-0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 29 publications
(36 reference statements)
4
22
0
4
Order By: Relevance
“…Hyperoside is quercetin-3-O-galactoside. It was found out in strawberries [Bagdonaite et al 2013], blueberries [Hicks et al 2012], whitethorn [Belkhir et al 2013] and rowan [Gaivelyte et al 2013]. Among herbs, it is abundant above all in St John's wort [Cirak et al 2013].…”
Section: Resultsmentioning
confidence: 99%
“…Hyperoside is quercetin-3-O-galactoside. It was found out in strawberries [Bagdonaite et al 2013], blueberries [Hicks et al 2012], whitethorn [Belkhir et al 2013] and rowan [Gaivelyte et al 2013]. Among herbs, it is abundant above all in St John's wort [Cirak et al 2013].…”
Section: Resultsmentioning
confidence: 99%
“…Separation of flavonols and phenolic acid was performed according to the methodology described by Gaivelyte et al [ 40 , 41 ] using an ACE (ACT, Aberdeen, UK) column (C18, 150 mm × 4.6 mm, particle size 3 μm). The mobile phase of the optimized chromatographic method consisted of eluent A (0.05% trifluoracetic acid) and B (acetonitrile).…”
Section: Methodsmentioning
confidence: 99%
“…Validation parameters—linearity and range of linearity, limits of detection and limits of quantification, intra-day repeatability and intermediate precisions, were assessed according to the ICH guidelines. The results of validation were described in our previous studies [ 40 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Gaivelyte et al analysed leaf and fruit material of 10 Sorbus spp. and 9 cultivars and found that the TPC varied approximately 5 times, both in leaf and fruit samples, i.e., in the range of 7.18–35.74 mg/g and 2.24–11.19 mg/g, respectively [ 56 ]. The berries of S. aria and S. aucuparia grown at different altitudes were compared; however, there was no correlation between TPC, total proanthocyanidins, radical scavenging capacity and growing site.…”
Section: Total Phenolic Content and Quantitative Composition Of Phmentioning
confidence: 99%